The Use of Cooperative Learning Type Jigsaw in Enhancing Students’ Reading Achievement - Nurchurifiani, Eva; Wahyuningsih, Sri; Alfiawati, Riska; Febrianti, Tri Iliona; Jejen, Muhammad (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
Generally, most of students have some problems in learning English, especially in learning reading. The problem in this research was the students don’t know yet kind of technique, strategies, method of learning reading. And also students have lack of vocabulary and grammar. And then the students got difficulties in comprehend the English text. The English teacher should have good method in teaching and learning English. The object of this research was to know the significant influence of Cooperative Learning Type Jigsaw towards students’ reading ability at the tenth grade of SMK Taman Siswa, Bandar Lampung in 2024/2025. Cooperative Learning Type Jigsaw improved students’ reading ability. The sample in this research were two classes, they were experimental class and control class. In the experimental class the writer used Cooperative Learning Type Jigsaw in teaching reading and the control class the writer used direct instruction. In the data collecting technique the writer used reading test, and used multiple choice. In the data analysis the writer used t-test formula.